2014
DOI: 10.1039/c4cp03355h
|View full text |Cite
|
Sign up to set email alerts
|

Rational modifications on champion porphyrin dye SM315 using different electron-withdrawing moieties toward high performance dye-sensitized solar cells

Abstract: Ten porphyrin sensitizers with different electron-withdrawing groups derived from the best sensitizer SM315 were investigated by means of the density functional theory (DFT) and time-dependent DFT calculations. To this end, major factors affecting the performance of the cell, including light harvesting, electron injection, dye regeneration, and conduction band energy shift are taken into consideration. Especially, the calculated distance (r) from the electron recapture center to the semiconductor surface is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 84 publications
(94 reference statements)
0
27
0
Order By: Relevance
“…However, to the best of our knowledge, TPz has only been examined in DSC dyes with both donor and acceptor groups substituted on the thiophene a single time potentially due to a synthetically challenging desymmeterization, which is needed to give directional electron flow across the molecule . Encouragingly, several computational reports are available with donor–acceptor substituted TPz bridges at the thiophene positions with interesting predicted properties such as increased absorption intensity, increased absorption breadth, and high tunability of dye energy levels. Only the donor–acceptor structural arrangement utilizes the proaromatic nature of the pyrazine ring for maximum light absorption according to valence bond theory.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, TPz has only been examined in DSC dyes with both donor and acceptor groups substituted on the thiophene a single time potentially due to a synthetically challenging desymmeterization, which is needed to give directional electron flow across the molecule . Encouragingly, several computational reports are available with donor–acceptor substituted TPz bridges at the thiophene positions with interesting predicted properties such as increased absorption intensity, increased absorption breadth, and high tunability of dye energy levels. Only the donor–acceptor structural arrangement utilizes the proaromatic nature of the pyrazine ring for maximum light absorption according to valence bond theory.…”
Section: Introductionmentioning
confidence: 99%
“…When charge separation distance is not enough to overcome the electrostatic attraction between electrons and holes and charge recombination occurs . The rate of charge recombination decreases with increasing distances between dye cation holes and TiO 2 surfaces (R) . As shown in Figure , the R decrease in the order of D3‐L4 (13.95 Å) > D3‐L3 (13.66 Å) > D3‐L2 (11.02 Å) > D3‐L1 (10.62 Å) > D3 (7.15 Å).…”
Section: Resultsmentioning
confidence: 85%
“…Here we want to bring it to readers notice that recent reports have shown that the Electron Withdrawing Groups (EWG), NTz of structure 39 containing two fused 1, 2, 5‐thiadiazole rings lower the band gap, enhance the inter‐chain packing and also improve the charge mobility in polymer studies . Besides Zhang et al in their computational study has recently predicted structure 39 as a promising candidate for DSC. However replacement of BTD with dithieno 3, 2‐b: 2′, 3′‐d pyrrole (in structure 35 and 36) has significantly lowered the potential of LUMO.…”
Section: Resultsmentioning
confidence: 93%